2014
DOI: 10.5146/tjpath.2014.01235
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic eosinophilic cholecystitis with cholelithiasis: a report of two cases

Abstract: ABSTRACTeosinophilic cholecystitis is a rare entity diagnosed on the basis of classical presentation of cholecystitis with presence of more than 90% eosinophilic infiltration within the gall bladder. The etiology of eosinophilic cholecystitis still remains obscure. However it is frequently associated with other more severe diseases like hypereosinophilic syndrome, eosinophilic-myalgia syndrome, parasitic infestations, few herbal medicines and certain drugs.we report two cases who presented with gall stone dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 2 publications
1
6
0
1
Order By: Relevance
“…When the infiltrate be formed of 50-75% eosinophils along with other inflammatory cells it is diagnosed as lympho-eosinophilic cholecystitis. [2,3,4] Similarly, in our study mostly transmural, dense, diffuse eosinophilic infiltrates and few lympocytes were seen in EC cases, histopathologically.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…When the infiltrate be formed of 50-75% eosinophils along with other inflammatory cells it is diagnosed as lympho-eosinophilic cholecystitis. [2,3,4] Similarly, in our study mostly transmural, dense, diffuse eosinophilic infiltrates and few lympocytes were seen in EC cases, histopathologically.…”
Section: Discussionsupporting
confidence: 79%
“…In some studies researchers found that patients with acalculous cholecystitis contain a higher percentage of eosinophils, histopathologicallly than in patients with gallstones. [2][3][4]7,11] In contrast, 78.9% of our cases had biliary stones and one of them had biliary mud.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Safra kesesi mukozasında diğer inflamatuvar hücreler ile birlikte %90'dan fazla eozinofilik infiltrasyonun bulunduğu olgular ise eozinofilik kolesistit olarak rapor edilmektedir ve kolesistektomi materyallerinin %20'ni oluşturmaktadır. Eozinofilik kolesistitin başlıca nedenleri hipereozinofilik sendrom, eosinofili-miyalji sendromu, parazitik enfeksiyonlar, bazı bitkisel ve diğer ilaçlardır [18,19]. Kronik kolesistitlerin mikroskopik özelliğe sahip bir diğer tipi ksantogranulomatöz kolesistittir.Makroskopik ve radyolojik olarak bazen malignite görüntüsü verebilir ve bu yüzden tanı sürecinde histopatoloji önem arz etmektedir [20].…”
Section: Kolelitiazisinunclassified